Peran Dukun dalam Implementasi Kemitraan Bidan dan Dukun di Wilayah Kerja Puskesmas Bangsalsari Kabupaten Jember (The Role of Traditional Birth Attendance in the Implementation of Partnership between Midwife and Traditional Birth Attendance at Bangsalsari - Devy Aristin S. Sofyan; Abu Khoiri; Eri Witcahyo (Pustaka Kesehatan, 2015)
One of factors that affected maternal death are skill and ability of delivery. According tothe data of Health Department of Jember District , the numbers of childbirth helped bytraditional birth attendance at the subdistrict area of Bangsalsari Community HealthCenter were 165 in 2012 and 102 childbirth in 2013. The goal of study was to describethe role of traditional birth attendance in the implementation of Midwife and TraditionalBirth Attendance Partnership in pregnancy and delivery period in BangsalsariCommunity Health Center, Jember District. The study was a qualitative study with haveinvolving 11 informants by Purposive technique. The result showed that traditional birthattendance have did some of their roles in pregnancy and delivery period. Pregnantmother have motivate traditional birth attendance to do check pregnancy and deliveryprocess to midwife but some of them did not have go to midwife to check pregnancy andpreferred to choose traditional birth attendance as their delivery. Unfortunately traditionalbirth attendances still help delivery process because there were some of people ask andforce them to assist delivery process.Keyword: Traditional birth attendance role, Partnership, Pregnancy, Delivery.